2020
DOI: 10.1111/jfpp.14470
|View full text |Cite
|
Sign up to set email alerts
|

Screening, identification, and application of selenium‐enriched Lactobacillus in goat milk powder and tablet

Abstract: In this study, Lactobacillus L20 was screened by measuring the tolerance to the inorganic selenium and the resistance to the gastrointestinal fluid of 11 Lactobacillus preserved in the laboratory. Next, the selenium‐enriched L20 was produced into the corresponding selenium‐enriched L20 goat milk powder and milk tablet. The storage stability of the prepared powder and tablet were investigated by the accelerated test. The results indicated that the conversion rate of inorganic selenium of L20 was 87.65% and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
(25 reference statements)
0
6
1
Order By: Relevance
“…In the present study, lower selenite concentrations did not accelerate the growth of either strain, unlike the effects reported in some previous studies [16,39]. Moreover, in LAB strains tested by Shu et al [14], viable counts decreased with the increase in sodium selenite concentration. In comparison, our results suggested that CCDM 144 may have a higher tolerance to sodium selenite than CCDM 922A because no reduction in viable counts was observed in the former strain even at the highest selenite concentration used (50 mg/L).…”
Section: Effects Of S Thermophillus Ccdm 144 and E Faecium Ccdm 922a Selenization On Cell Viability And Growthcontrasting
confidence: 85%
See 1 more Smart Citation
“…In the present study, lower selenite concentrations did not accelerate the growth of either strain, unlike the effects reported in some previous studies [16,39]. Moreover, in LAB strains tested by Shu et al [14], viable counts decreased with the increase in sodium selenite concentration. In comparison, our results suggested that CCDM 144 may have a higher tolerance to sodium selenite than CCDM 922A because no reduction in viable counts was observed in the former strain even at the highest selenite concentration used (50 mg/L).…”
Section: Effects Of S Thermophillus Ccdm 144 and E Faecium Ccdm 922a Selenization On Cell Viability And Growthcontrasting
confidence: 85%
“…LAB also represent a promising target group for selenization [14][15][16], as these microbes produce various antimicrobial compounds such as organic acids, hydrogen peroxide, and bacteriocins, which possess antimicrobial activity by means of the different metabolic substances generated [17]. However, as Se-enriched LAB are not yet legislatively permitted for use in foods, it is necessary to obtain additional information regarding their safety, functionality, and properties.…”
Section: Introductionmentioning
confidence: 99%
“…The selenium concentration in the medium is highly linked to bacterial selenium level, but the growth of most bacterial isolates from the human gut can be inhibited by the addition of inorganic selenium into the medium [ 20 ]. However, some LAB strains have been reported to be capable of resisting selenium oxyanions at high concentrations during cultivation [ 21 , 22 , 23 ]. Especially, Lactobacillus plantarum has been suggested as Se-enriched lactobacilli for food applications [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Shu et al. (2020) produced Se‐enriched probiotic goat milk as powder and tablets. Lactobacillus has the potential to bio‐convert Se from inorganic to organic forms, such as selenocysteine (Alzate et al., 2007; Alzate et al., 2010; Morschbacher et al., 2018; Xu et al., 2020), which is safer and has higher nutritional value and bioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…The method used in this study considered encapsulated method by using skimmed milk as a carrier for Se in NPs form (Hassan et al, ,2014;Hassan et al, ,2011;Salama et al, 2015). Finally, Shu et al (2020) produced Se-enriched probiotic goat milk as powder and tablets. Lactobacillus has the potential to bio-convert Se from inorganic to organic forms, such as selenocysteine (Alzate et al, 2007;Alzate et al, 2010;Morschbacher et al, 2018;Xu et al, 2020), which is safer and has higher nutritional value and bioactivity.…”
Section: Introductionmentioning
confidence: 99%